Bilateral glenohumeral septic arthritis secondary to mastitis with subsequent avascular necrosis: A case report. (November 2021) - Maranya, Samora Onsare; Mutiso, Vincent Muoki
Abstract: Introduction and importance: Septic arthritis is an orthopaedic emergency. Only 3% of septic arthritis patients present with glenohumeral involvement. Polyarticular disease with shoulder involvement constitutes 1% of this group. There is currently no documented case of bilateral glenohumeral septic arthritis with avascular necrosis secondary to mastitis. Case presentation: We present a case of a 38-year-old African woman with bilateral glenohumeral septic arthritis after management for mastitis of the left breast. She had left, then right shoulder pain, fever, and reduced range of motion, with multiple arthroscopic washouts and antibiotic therapy instituted at various hospitals by various specialists, leading to the resolution of active infection. The patient developed bilateral humeral head avascular necrosis with complete collapse as evidenced on plain radiography 4 months later, and underwent hemiarthroplasty of the right shoulder. Biopsy at operation showed no active bone infection, and inflammatory markers were not elevated. She had reduced discomfort for the following 2 years but developed increasing pain on lifting and reduced range of motion. The moderate symptoms in her left shoulder managed non-operatively had remained unchanged. There were no elevated inflammatory markers 2-years post arthroplasty. Clinical discussion: This case presents an uncommon scenario of bilateral septic arthritis secondary to mastitis, with rapid progression to avascular necrosis in an individual with no classical risk factors for avascular necrosis, despite appropriate antibiotic treatment and surgical interventions. Advanced collapse necessitated hemiarthroplasty of the dominant right side. Conclusion: This case highlights the need for close radiographic follow-up in atypical presentations of septic arthritis and the dilemmas in managing advanced bilateral avascular necrosis with arthroplasty in a young patient. Highlights: Septic arthritis is an orthopaedic emergency. Mortality rates for septic arthritis range from 4 to 42% in monoarticular disease and up to 50% in polyarticular involvement. Only 3% of septic arthritis cases are glenohumeral, with 1% being polyarticular. Humeral head avascular necrosis secondary to septic arthritis is rare.